Public views of the economy of the renewable energy sources: Evidence from Russia - Dalia Štreimikienė; Victoria Akberdina (Contemporary Economics, 2021)
Recent worldwide growing awareness of the global climate changes stressed the importance of developing and supporting the renewable energy sources (RES). However, the public support for RES varies across various countries and regions, especially those abundant in traditional fossil fuels. This paper presents the analysis of the public views of the economics of the renewable energy using the results of the online survey (N = 750) conducted in several regions of the Russian Federation, a country abundant in natural gas and oil. Our results indicate that there is a mixed opinion on trust in RES as opposed to the traditional energy sources. Even though we found some support for the renewable energy technologies, it appears that it is correlated with the respondents' concerns about the environmental protection and sustainable development as well as with some demographic variables. The outcomes of the regression analysis confirmed that positive attitudes towards climate protection predetermined the support for various types of RES, while the financial or political gains did not come through as significant. The results indicate that public views on the renewable energy sources could and should be shaped by the information campaigns and presentations in mass media conducted by relevant policymakers and public authorities.
Keywords: H30; P18; Q20; Q30; 330; Renewable energy; fossil fuels; public opinion; energy policy; energy economics; Russia